PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PESANAN PADA PT.TOBECO - Sari, Dian Indah (www.bsi.ac.id, 2018)
ABSTRACTThe purpose of this study is to calculate the cost of production using the cost of the order of invitations, advertisements and brochures on PT.Tobeco.Metode research used in this study include interviews that data obtained by interview directly to the company. Interviews are done by direct interviews to the company's chairman and the part directly involved with the research title. Literature study is data obtained by reading literature study of books and journals to obtain theories associated with the title of research. Data analysis is analyzing the data obtained and preparing reports on the cost of orders and income statement. Based on the calculation of cost of goods manufactured by the cost of order method at PT. Tobeco can be summarized as followsThe company will get the lowest order price if they receive the brochure order and get the highest order price if receiving advertising order. The cost of order per unit for invitation is Rp 4,060 per share. The order per unit price for advertising is Rp 9,100 per share. The order per unit price for brochures is Rp 1,172 per share. The company will get the highest gross profit if it receives brochure orders and gets the lowest gross profit if it receives an advertising order. The invitation order earns a gross profit of Rp 4.700.000. Ad orders earn a gross profit of Rp 2.700.000. Brochure orders earn a gross profit of Rp 41.4 million.Keywords: Cost of Production, Cost of Order